A Metaanalysis of the relationship between growth mindset and mental health in Chinese samples - Xiaoli Yang; Jianmei Yang; Tingting Jia; Lin Wang; Jing Zhang (Acta Psychologica)
Innovations in mental health are desperately needed in Healthy China with increasing benefits of a growth mindset on mental health among Chinese. Currently, empirical research in China reveals significant discrepancies in the correlation between growth mindset and mental health. To elucidate this discrepancy, we conducted a meta-analysis on 59 studies utilizing a random-effects model, with 68 effect sizes and 54,302 participants included. The main effects revealed a significantly positive correlation between growth mindset and positive indicators of mental health (r = 0.36, [0.27, 0.45]), as well as a significantly negative correlation between growth mindset and negative indicators of mental health (r = −0.25, [−0.31, −0.20]). Subgroup test and meta-regression results indicated that age, economic region, and measurement instruments moderated the growth mindset and positive indicators of mental health. In contrast, negative indicators were moderated by gender and measurement instruments. The above findings suggest that a growth mindset significantly correlates with mental health. Consequently, it can be developed into an effective psychological service strategy in Healthy China. Future empirical studies should continue to examine this relationship and explore additional potential moderating variables. Furthermore, the clinical effects of growth mindset interventions in mental health should be tested.